2023
DOI: 10.1109/ojcoms.2023.3310003
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble-Based IoT-Enabled Drones Detection Scheme for a Safe Community

Jaskaran Singh,
Keshav Sharma,
Mohammad Wazid
et al.

Abstract: With the increasing use of Internet of Things (IoT)enabled drones for various purposes, including photography, delivery, and surveillance, concerns related to privacy and security have arisen. Drones have the potential to capture sensitive information, invade privacy, and cause security breaches. Therefore, the need for advanced technology for the automated detection of drones has become crucial. In this paper, we propose an ensemble-based IoT-enabled drones detection scheme (in short, EDDSBS). The presented m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the proposed cost-effective system can perform real-time drone detection with zero false negative (FN) outcomes. An ensemble-based IoT-enabled drone detection approach using transfer learning and background subtraction was proposed in [ 87 ]. The ensemble model includes two DL models: YOLOv4 and ResNet-50.…”
Section: Drone Detection Technologiesmentioning
confidence: 99%
“…The experimental results showed that the proposed cost-effective system can perform real-time drone detection with zero false negative (FN) outcomes. An ensemble-based IoT-enabled drone detection approach using transfer learning and background subtraction was proposed in [ 87 ]. The ensemble model includes two DL models: YOLOv4 and ResNet-50.…”
Section: Drone Detection Technologiesmentioning
confidence: 99%